Ubiquitin‐dependent regulation of Foxp3 and Treg function. Issue 1 (July 2015) - Barbi, Joseph; Pardoll, Drew M.; Pan, Fan
Summary: Regulatory T (Treg) cells are crucial enforcers of immune homeostasis. Their characteristic suppressive function largely arises from an equally unique pattern of gene expression. A complex network of factors and processes contribute to this 'signature' Treg gene expression landscape. Many of these alter the level and activity of the Treg‐defining transcription factor Foxp3. As stable expression of Foxp3 is important for the ability of Treg cells to successfully prevent excessive or inappropriate immune activation, uncovering the mechanisms regulating Foxp3 level is required for the understanding and therapeutic exploitation of Tregs. While transcriptional regulation of the Foxp3 gene has been studied in depth, additional regulatory layers exist controlling the expression and activity of this key transcription factor. These include less‐defined mechanisms active at the post‐translational level. These pathways are just beginning to be elucidated. Here, we summarize emerging evidence for distinct, post‐translationally active, ubiquitin‐dependent pathways capable of controlling the activation and expression of Foxp3 and the function of Tregs. These pathways offer untapped opportunities for therapeutic fine‐tuning of Tregs and their all‐important restraint of the immune system.